Successful Treatment of Cerebral Tuberculoma and Tuberculous Lymphadenitis in an HIV/AIDS Patient: A Case Report - Tenta Hartian Hendyatama; Usman Hadi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Tuberculosis is one opportunistic infection that may occur in HIV/AIDS patients. Its clinical presentation may depend on infected organs. A 37-years old man complained of left limb weakness followed by mild fever, weight loss of more than 10 kgs within two months, and swelling in his left submandibular region. Laboratory tests showed mild anemia, hypoalbuminemia, and positive serology HIV test. Histopathological examination of neck swelling showed inflammation of chronic granulomatous tuberculous with acid-fast bacilli positive in Ziehl Nielsen staining. Head CT scan with contrast, showed multiple isodense lesions with rim contrast enhancement accompanied by perifocal edema. Anti-Tuberculosis Drug and Anti-Retroviral Therapy were given as a combination treatment for this patient. Clinical and radiological improvement in the patient indicated good outcome and successful treatment.